Contagious Im/Possibilities: Infectious Encounters in Austin Clarke’s The Meeting Point - Wong, Danielle (Studies in Canadian Literature, 2013)
Set in Toronto, during an era of changing immigration policies under the 1955 West Indian Domestic Scheme and ongoing revisions to the 1952 Immigration Act, Austin Clarke’s novel The Meeting Point (1967) provides an insightful entry point for the exploration of the intersections of race, disease, (post)colonialism, and citizenship. The "meeting points" in the text call for a critical analysis of the embodied exposures — the instances of bodies’ reciprocal infection, inoculation, and staining — described in this story of West Indian domestics working for Jewish families in the 1960s. The cross-racial encounters portrayed in The Meeting Point are transmissions of contagion, in which the virus of colonial and imperial residue — the living histories and effects of violence and oppression — exposes the impossibility of static ethnic identities and the unstable interconnectedness of marginalities transmitted between displaced subjects. The novel’s complex treatment of domestic-employer relationships simultaneously echoes and challenges the imperial discourses of public health in order to unveil past and present realities that trouble narratives of national progress. This article examines the metaphor of contagion in The Meeting Point by discussing miscegenation as a form of racial vaccination and the (non)reproductive body of the Other as a subversive contamination of the modern nation.